Indigenous engagement in health: lessons from Brazil, Chile, Australia and New Zealand - Angeline Ferdinand; Michelle Lambert; Leny Trad; Leo Pedrana; Yin Paradies; Margaret Kelaher (BMC, 2020)
Abstract Background Given the persistence of Indigenous health inequities across national contexts, many countries have adopted strategies to improve the health of Indigenous peoples. Governmental recognition of the unique health needs of Indigenous populations is necessary for the development of targeted programs and policies to achieve universal health coverage. At the same time, the participation of Indigenous peoples in decision-making and program and policy design helps to ensure that barriers to health services are appropriately addressed and promotes the rights of Indigenous peoples to self-determination. Due to similar patterns of Indigenous health and health determinants across borders, there have been calls for greater global collaboration in this field. However, most international studies on Indigenous health policy link Anglo-settler democracies (Canada, Australia, Aotearoa/New Zealand and the United States), despite these countries representing a small fraction of the world's Indigenous people. Aim This paper examines national-level policy in Australia, Brazil, Chile and New Zealand in relation to governmental recognition of differential Indigenous health needs and engagement with Indigenous peoples in health. The paper aims to examine how Indigenous health needs and engagement are addressed in national policy frameworks within each of the countries in order to contribute to the understanding of how to develop pro-equity policies within national health care systems. Methods For each country, a review was undertaken of national policies and legislation to support engagement with, and participation of, Indigenous peoples in the identification of their health needs, development of programs and policies to address these needs and which demonstrate governmental recognition of differential Indigenous health needs. Government websites were searched as well as the following databases: Google, OpenGrey, CAB Direct, PubMed, Web of Science and WorldCat. Findings Each of the four countries have adopted international agreements regarding the engagement of Indigenous peoples in health. However, there is significant variation in the extent to which the principles laid out in these agreements are reflected in national policy, legislation and practice. Brazil and New Zealand both have established national policies to facilitate engagement. In contrast, national policy to enable engagement is relatively lacking in Australia and Chile. Australia, Brazil and New Zealand each have significant initiatives and policy structures in place to address Indigenous health. However, in Brazil this is not necessarily reflected in practice and although New Zealand has national policies these have been recently reported as insufficient and, in fact, may be contributing to health inequity for Māori. In comparison to the other three countries, Chile has relatively few national initiatives or policies in place to support Indigenous engagement or recognise the distinct health needs of Indigenous communities. Conclusions The adoption of international policy frameworks forms an important step in ensuring that Indigenous peoples are able to participate in the formation and implementation of health policy and programs. However, without the relevant principles being reflected in national legislature, international agreements hold little weight. At the same time, while a national legislative framework facilitates the engagement of Indigenous peoples, such policy may not necessarily translate into practice. Developing multi-level approaches that improve cohesion between international policy, national policy and practice in Indigenous engagement in health is therefore vital. Given that each of the four countries demonstrate strengths and weaknesses across this causal chain, cross-country policy examination provides guidance on strengthening these links.